2010
DOI: 10.1590/s0100-204x2010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de formas aladas de pulgões e sua relação com fatores meteorológicos e plantas hospedeiras

Abstract: Resumo -O objetivo deste trabalho foi determinar o padrão de revoadas e a infl uência de fatores meteorológicos e de Brassicaceae sobre populações de formas aladas dos pulgões Brevicoryne brassicae, Lipaphis erysimi e Myzus persicae. Os pulgões foram amostrados em armadilhas tipo bandeja amarela com água, entre julho de 1997 e agosto de 2005. A correlação parcial de Pearson foi utilizada para verifi car a infl uência da temperatura do ar, umidade relativa, chuva e insolação na abundância de alados das três esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…These species also showed the same predictor, i.e., number of days with rainfall. This result is in accordance with Cividanes & Santos-Cividanes (2010), which reported that L. erysimi and M. persicae showed similar flight dynamics, differing from B. brassicae. These authors also found that B. brassicae showed a significant correlation with maximum and minimum temperatures, sunshine hours, and air relative humidity, whereas L. erysimi and M. persicae were only affected by sunshine and relative humidity.…”
Section: Speciessupporting
confidence: 93%
See 2 more Smart Citations
“…These species also showed the same predictor, i.e., number of days with rainfall. This result is in accordance with Cividanes & Santos-Cividanes (2010), which reported that L. erysimi and M. persicae showed similar flight dynamics, differing from B. brassicae. These authors also found that B. brassicae showed a significant correlation with maximum and minimum temperatures, sunshine hours, and air relative humidity, whereas L. erysimi and M. persicae were only affected by sunshine and relative humidity.…”
Section: Speciessupporting
confidence: 93%
“…According to Cividanes & Santos-Cividanes (2010), the occurrence of the alate B. brassicae was restricted from May to October-November, and no specimens were captured from December to April of the following year. However, the alates L. erysimi and M. persicae were observed for a longer period than B. brassicae, especially L. erysimi, which was captured in most of the evaluated months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the non-irrigated area (Figure 5B), this correlation becomes strongly negative (-0.7) and this result suggests that the higher the RH of the air, the lower the aphid populations, creates a microclimate over the leaf canopy, increasing the relative humidity of the air close to this layer. A strong negative correlation between aphid populations and relative air humidity was verified by Cividanes and Cividanes (2010) and Ramos et al (2018) who indicate that this result may occur due to the pattern of variation in the population density of different species of aphids being linked to numerous factors that contribute to differences in their population dynamics. Honek (1985) confirms that aphid species are similarly influenced by meteorological factors and have similar characteristics in abundance and preference for favorable microclimates.…”
Section: Resultsmentioning
confidence: 78%